THE IMPACT OF DIETARY SUPPLEMENTS ON THE HUMAN BODY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The paper investigates the essential elements regarding dietary supplements (DS) by studying both their advantages and disadvantages. The article discusses dietary supplements (DS) through their applications for hypodynamia cases and stress management together with exogenous toxicity concerns and diet imbalance issues and extended life expectancy challenges. Investigational studies of dietary supplements' human body effects remain essential due to their extensive use in nutrition science and clinical dietetics and sports medicine.